Environmental quality, infant morality, and economic growth in selected sub-Saharan African countries - Busayo Aderounmu; Adedoyin Awofiranye; Olubusayo Emmanuel Oni (Comparative Economic Research. Central and Eastern Europe, 2023)
Beyond the usual macroeconomic stability, which is a necessity for economic growth, more focus should be placed on the effects that environmental quality has on infant mortality in sub-Saharan Africa. Africa has always had the highest rate of infant mortality and the poorest environmental quality in the world. High infant mortality shows that there are unmet human needs and unenforced policies to protect the environment. Therefore, this research examines the impact of environmental quality on infant mortality and how environmental quality and infant mortality also affect economic growth using 15 selected sub-Saharan African countries for a period of 10 years (2010-2019). The study employed fixed and random effects methods of estimation. The results showed that environmental quality has a significant negative (51.53%) impact on infant mortality and that economic growth also has a negative (45.58%) impact on infant mortality. The study recommends that governments should increase expenditure on health, with more focus on financing infant healthcare, because it also affects economic growth.
Keywords: O44; I15; N17; Q53; 330; Environmental quality; infant mortality; economic growth; sub-Saharan African